2021
DOI: 10.17762/turcomat.v12i3.1569
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Usability of the MediCare System

Abstract: Smartphones, digital medical devices, smart bracelets, and mobile applications have emerged in the healthcare field as an effective way to help in the treatment of patients. Healthcare services are characterized by ease of use, low cost, accessibility, mobility, and reliability. The MediCare system was built to enhance healthcare services in the Iraqi environment. The MediCare system can run on smartphones or tablets that operate on Android, but it can also be used as a web application. The research team wante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The usability testing results showed that the native G-MoMo applications were helpful because their features allowed mobile money subscribers to register, deposit money, withdraw money, send money, update their mobile money PINs and biometric fingerprints, and so on. This is consistent with the studies conducted by and Al-Gayar et al (2021), where they found the applications helpful in achieving their goals.…”
Section: Heuristic Evaluation and Usability Testing (I) Several Usabi...supporting
confidence: 90%
See 2 more Smart Citations
“…The usability testing results showed that the native G-MoMo applications were helpful because their features allowed mobile money subscribers to register, deposit money, withdraw money, send money, update their mobile money PINs and biometric fingerprints, and so on. This is consistent with the studies conducted by and Al-Gayar et al (2021), where they found the applications helpful in achieving their goals.…”
Section: Heuristic Evaluation and Usability Testing (I) Several Usabi...supporting
confidence: 90%
“…The mobile money subscribers were satisfied with the features and functionalities of the G-MoMo applications, the information, and the display quality. This attribute was reported in other studies conducted by Byun et al (2020) The new mobile money subscribers found it easy to use the native G-MoMo applications because of the simplicity of the interfaces, features, and functionalities, which helped achieve total satisfaction (Byun et al, 2020;Merks et al, 2020;Lersilp et al, 2020;Sukmasetya et al, 2020;Al-Gayar et al, 2021;Kairy et al, 2021).…”
Section: Heuristic Evaluation and Usability Testing (I) Several Usabi...supporting
confidence: 59%
See 1 more Smart Citation
“…The mobile money subscribers were satisfied with the features and functionalities of the G-MoMo applications, the information, and the display quality. This attribute was reported in other The new mobile money subscribers found it easy to use the native G-MoMo applications because of the simplicity of the interfaces, features, and functionalities, which helped achieve total satisfaction (Byun et al, 2020;Merks et al, 2020;Lersilp et al, 2020;Sukmasetya et al, 2020;Al-Gayar et al, 2021;Kairy et al, 2021).…”
Section: Heuristic Evaluation and Usability Testingmentioning
confidence: 65%